An Evaluation of Internal Quality Audit Standards for Learning: Identifying Areas for Improvement in a Higher Education Institution - Manueke, Selfy; Dua, Iyaam L.; Manopo, Meiske W.; Sinaga, Floren Agnesia; Tumengkol, Inka M.S. (International Ecsis Association, 2026)
Internal quality assurance has become a critical mechanism for improving learning quality in higher education institutions, yet the effectiveness of internal quality audits often depends on how clearly learning standards are structured and implemented within institutional audit systems. This study aims to investigate the existing internal quality audit (IQA) standards for learning at Manado State Polytechnic and to identify areas for improvement. This research employed a qualitative approach by collecting data through document analysis and semi-structured interviews. A total of 15 informants participated in the study, including the head and administrators from the Learning Development and Quality Assurance Center, study program coordinators, and internal auditors. The findings indicate that the internal quality audit process at Manado State Polytechnic follows a three-stage model. However, the quality standards used in the audit application system are unsystematically organized and inconsistently arranged across study programs. Moreover, several essential learning components are not comprehensively included in the quality standards, such as curriculum design, teaching and learning methods, assessment and evaluation, student support and engagement, and lecturers’ performance. These limitations contribute to inefficiencies in the current internal quality audit implementation. This study suggests the reorganization of the quality standards into a chronological framework of “Before Learning,” “During Learning,” and “After Learning” to simplify evidence submission and audit processes. This study contributes to internal quality assurance practices by providing practical insights for quality assurance managers in developing more systematic and effective internal quality audit standards to support continuous improvement in learning quality.